PS-BPC02-6: ASSOCIATION BETWEEN MAJOR ADVERSE CARDIOVASCULAR EVENTS AND GENSINI SCORE IN HYPERTENSIVE PATIENTS WHO UNDERWENT CORONARY COMPUTED TOMOGRAPHY ANGIOGRAPHY. (January 2023) - Miura, Shinichiro; Miura, Erika; Higashi, Sara; Tashiro, Kohei; Kawahira, Yuto; Shiga, Yuhei
Abstract : Objective: From the Fukuoka University coronary computed tomography angiography (FU-CCTA) registry, we present major cardiovascular events (MACEs) in hypertensive patients who underwent CCTA, and the association between MACE and Gensini score of coronary arteries. Design and method: Of the patients who underwent CCTA for the purpose of screening for CAD at Fukuoka University Hospital (FU-CCTA registry), 318 hypertensive patients with suspected CAD or at least one cardiovascular risk factor were enrolled. A severity of atherosclerosis of coronary arteries was assessed by the Gensini score. The coronary artery calcification score (CACS) was defined as the presence of two or more contiguous pixels with more than 130 Hounsfield Units on CT images at the time of CCTA. MACEs (all-cause death, ischemic stroke, acute myocardial infarction, coronary revascularization) was a primary endpoint for the follow-up of patients for up to 5 years. The patients were divided into two groups according to the presence (MACEs group) or absence (non-MACEs group) of MACEs. Results: The average age was 68 ± 10 years and 50 % were males. The percentages of smoking, dyslipidemia, diabetes and chronic kidney disease were 37 %, 70 %, 26 % and 35 %, respectively. The %males, %smoking, CACS and Gensini score in the MACEs group were significantly higher than that in the non-MACEs group, whereas there were no differences in age, dyslipidemia, diabetes and chronic kidney disease between the groups. Regarding the relationships between MACEs and various coronary risk factors, CACS or Gensini score by a Cox regression analysis, significant relationships were observed for the CACS (p = 0.019) and the Gensini score (p = 0.002). Conclusions: CACS or Gensini score could be a predictor of MACEs in hypertensive patients who underwent CCTA.